Antibacterial activity from tuber of Ampelocissus Cinnamomea Merr in their sequential solvent extract - Tan Huey Yee (2022)
The current study was carried out to explore and analyze the potential of antibacterial activity in the tuber of Ampelocissus cinnamomea by the screening of selected Gram-positive bacteria viz., S. aureus, Methicillin-resistant Staphylococcus aureus, B. cereus, B. subtilis, and Gram-negative bacteria viz., K. pheumoniae, E. Coli, and Y. enterocolitica against agar plug diffusion assay. The maceration technique was used to extract the antibacterial agent from the dried tuber of A. cinnamomea according to 5 sequence chemical solutions extract according to increasing polarity, which are hexane, chloroform, ethyl acetate, acetone, and methanol. Disc diffusion susceptivity test was used to examine the antibacterial activity of the extract. The results indicated that all used microorganisms were susceptible to the plant extracts. The hexane, chloroform, ethyl acetate, and acetone extracts of A. cinnamomea revealed a significant difference (p < 0.05) in this study. The result revealed that the extracts exhibit more inhibitory activities towards Gram-negative bacteria compared to Gram-positive bacteria. The highest percentage of the inhibitory potential of extract which showed the most promising antibacterial activity are ethyl acetate, acetone, and methanol as they can inhibit all the tested bacteria used in this study. Furthermore, phytochemical screening was done using preliminary screening of a group of organic compounds on TLC plates developed through a solvent system of ethyl acetate: methanol: petroleum ether with ratio 1:1:1 (v/v/v) sprayed with the respective reagent. Results of the preliminary screening of a group of compounds showed the presence of phenol, alkaloid, flavonoid, anthraquinone, and lactone. Ethyl acetate, acetone, and methanol extract of the tuber of A. cinnamomea showed the most diverse group of compounds as these three solvent extracts showed the presence of phenol, flavonoid, alkaloid, anthraquinone, and lactone compounds. The data from this study revealed the prominent antibacterial potential from the tuber of A. cinnamomea that can be used for further exploration and development of novel antibacterial from natural sources to improve human health.